Blueprint of the distinct metabolite profiles of healthy pig heart chambers - Haikonen, Retu; Meuronen, Topi; Koistinen, Ville; Kärkkäinen, Olli; Tuomainen, Tomi; Solano-Aguilar; Gloria; I; Urban Jr, Joseph F.; Lehtonen, Marko; Tavi, Pasi; Hanhineva, Kati (Elsevier BV, 2025)
The heart is one of the most studied organs, with physiological processes and disease research. While it is well-established that significant structural and functional differences exist between the chambers, most studies focus on only a single heart chamber, predominantly the left ventricle. This study aims to comprehensively characterise the chamber-specific metabolic profiles of all four heart chambers in a healthy animal model close to human metabolism, pigs. We employed liquid chromatography-mass spectrometry metabolomics to analyse the metabolite profiles of heart chambers in healthy pigs (N = 30) maintained on an ad libitum diet and housed under standard, non-stressed physiological conditions. Our findings reveal a higher energy demand in the left ventricle, as evidenced by elevated levels of electron transport chain-related metabolites such as NAD+ and FAD. Additionally, hexose-phosphates and several acylcarnitines exhibited chamber-dependent variations in abundance. The ventricles, particularly the left, demonstrated distinct redox states, with differential levels of glutathione and ascorbic acid, suggesting variations in oxidative stress across chambers. Furthermore, amino acids had chamber-specific abundance patterns, and ventricles showed an increased requirement for protein synthesis, likely associated with repair mechanisms following reactive oxygen species (ROS)-induced cellular damage. Our study reveals significant differences in the metabolic profiles across four heart chambers in healthy pig hearts, underscoring the metabolic heterogeneity of cardiac tissue. These findings highlight the necessity of investigating chamber-specific metabolic pathways to better understand heart functionality. Such insights could inform the development of more precise therapeutic strategies tailored to metabolic demands and functional roles in heart chambers.